Analisis Macam-Macam Illah Dalam Puisi Arab - Ramadhani, Fithri Salsabila; Hemawati, Hermawati; Rohmah, Intan Atala; Ridwan, Nur Anisah (Prosiding Konferensi Nasional Bahasa Arab, 2023)
Classical Arabic poetry is very structured in terms of the number of syllables in each line, and the science of 'arudh helps in organizing the number of syllables. 'Arudh and qawafi, zihaf and 'illat are intertwined elements in classical Arabic poetry. Zihaf is one type of 'arudh or metre used in poetry, which includes metrical patterns based on the number of syllables in each line, while 'illah refers to the reason or motive underlying the creation of a poem. In Arabic poetry, poets often express their feelings, thoughts, or messages through their poems, and 'Illah is their way of explaining why they wrote a particular poem. This article discusses how 'Illah studies in Arabic poetry, where poets use the Zihaf metre to express their 'Illah through rhythmic and rhyming structures. This concept is an important element in classical Arabic poetry and provides insight into how poets create rich and structured works in the Arabic poetic tradition.